After legalization: Cannabis, environmental compliance, and agricultural futures. (March 2023) - Polson, Michael; Bodwitch, Hekia; Biber, Eric; Butsic, Van; Grantham, Theodore
Abstract: As the largest polity worldwide to legalize cannabis, California has implemented uniquely high environmental and land use standards for cannabis agriculture. To date, however, regulations have suffered from low compliance rates, especially among smaller, "legacy" farms that existed prior to legalization. Meanwhile, both licensed and unlicensed farms are increasing in size, thus increasing environmental pressures. Is there a way to achieve environmental objectives, farmer compliance, and an equitable transition away from illegal markets? In the largest US survey of cannabis farmers to date, we found farmers are open to strong environmental protections yet face significant barriers in meeting regulatory requirements. We present this opinion article to suggest several strategies to ameliorate compliance barriers by reducing associated learning, financial, and psychological costs. Taken together, these strategies present an unprecedented opportunity to model a new kind of agriculture centered on small-farm production and environmental stewardship—a model that indicates new directions for agriculture beyond cannabis. Highlights: California cannabis regulations have struggled to enroll and support farmers, particularly at smaller scales. Barriers to and burdens of participation are key reason for non-participation. Policy responses should lower barriers and burdens in ways that support equity and sustainability. Policy responses should address financial, administrative, and psychological costs of legal market participation. If successful, cannabis policy may be model for agricultural policy in time of socio-environmental crisis.